Transplantation of ventral mesencephalic anlagen to hosts with genetic nigrostriatal dopamine deficiency. - Triarhou, L C (1986)
Attempts to reconstruct the damaged nigrostriatal pathway in experimental models of Parkinson disease have thus far been carried out in animals with neurotoxically induced dopamine deficiency. The present study establishes the weaver (wv/wv) mutant mouse as a genetic model of chronic striatal dopamine denervation by demonstrating a marked decrease of tyrosine hydroxylase-immunoreactive neurons in the substantia nigra pars compacta. Moreover, grafts of embryonic ventral mesencephalon taken from genetically normal mice and transplanted into the lateral ventricle of adult weaver mutants can survive and grow in the mutant host environment, express tyrosine hydroxylase immunoreactivity, and reinnervate the target regions of the recipient. These results provide evidence of integration of graft and host tissue and suggest that transplantation of dopamine neurons may be effectively applied to overcome nigrostriatal degeneration of genetic etiology.